Echoes of Waste: Eco-Conscious Fashion Expression in the Spirit of Pramoedya Ananta Toer - Wulansari, Vita; Jaya Putra, I Gede; Patricia Putra, Evelyn (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2025)
This work serves as a visual expression rooted in deep concern over environmental exploitation and the ongoing degradation of marine ecosystems. Through a sustainable fashion approach, this couture garment is crafted using post-consumer materials such as discarded denim, damaged compact discs, and plastic bottles, serving as a critical response to the consumerist culture that negatively impacts nature. The research adopts a descriptive qualitative method, utilizing the stages of exploration, experimentation, and formation as outlined by Alma M. Hawkins. It also incorporates the humanistic philosophy of Pramoedya Ananta Toer as a cultural lens to frame the narrative. The creative process reveals that fashion design can be a powerful medium for ecological critique, offering an alternative narrative that fosters collective environmental awareness. This work affirms that fashion is not merely about visual aesthetics, but also a space of resistance—one that advocates for humanity and sustainability.